Вы находитесь на странице: 1из 21

( )

.

4 10-

(2004-2005 )

. , 2004

2004, . .

2004-2005 . . 4 10 . . -. . -.

: .. ,
.

: 4 10- (2004-2005 ). - .:
, 2004, 31.

:

. . 040060 21.08.96. 09.12.04
6090 1/16. . . . . . 1,93
.-. . 1,72. 2300. 10-.
-
-
( )
-
141700, . ., . , ., 9
, / (095) 408-5145
./ (095) 485-4227 -
.409-9583
E.mail: zftsh@pop3.mipt.ru
: www.school.mipt.ru
-
( ), 2004
, 2004
., 2004

2004, . .

2004-2005 . . 4 10 . . -. . -.

1. .
X Y - . , X
, , x
X y Y .
- ,
f , f : X Y y = f ( x ).
x X ,
f ( x ). X

D( f ). Y ,
X , X ,
f ( x ), f ( X ) Y , E ( f ) Y .

x2

y1

x1

y2

X xn

f(X)

yn

. 1.

f ( x1 ) = y1 , f ( x2 ) = y1 , f ( xn ) = y2 .
X
Y ( y1 = f ( x2 ) = f ( x1 )),
X Y .
, . 1

1.
. X ,
f ( X ) 4- . ,
X .
2.
. X , 1, f ( X )
. , !
, ,
, X , Y ,
, . f ( X )

E ( f ).
3. ( . 2).
) g : R+ {0} R : y =

x ( D( g ) = R+ {0}, E ( g ) = R+ {0}).
1
) f : ( ;0 ) (0;+ ) R : y = . ( E ( f ) = ( ;0 ) (0;+ )).
x
) f : R R : y = x (, x).

x, x 0;
(D( f ) = R, E ( f ) = [0;+ ) R+ {0}).
x =
x, x < 0.
1, x > 0;

) y = signx 0, x = 0; D ( y ) = R, E ( y ) = { 1,0,1}. (

1, x < 0.
, ).

2004, . .

2004-2005 . . 4 10 . . -. . -.

y = f ( x )
(x, f ( x )).

(x, y )

)
. 2

4. y = [x ] x. [x ]
, x.
x [0;1), [x ] = 0. x [1;2 ), [x ] = 1. x [2;3), [x ] = 2

.. x. x [ 1;0 ),

[x] = 1.

x [ 2;1), [x ] = 2 ..

.3. , D ( f ) = R; E ( f ) = Z (
).
y = f ( x )
, x,
.
5.
) y = x 2 (. . x 2
x , D ( y ) = R;
).
) y = x 2 , D( y ) = [0;+ ) (
x =

y ).

) y = sin x ( D ( y ) = R ,
).


(
;
2 2
x = arcsin y ).

) y = sin x, D( y ) =

. 3

2004, . .

2004-2005 . . 4 10 . . -. . -.

) ) , . .
, !
) ).

y
y = x2
x

y
y = sin x


;
2 2

) y = sin x, x

)
. 4

2.
f : X f ( X ) E ( f ) (
, Y , ,
x X ) ,
x X y = f ( x ) Y , . . x1 x2 ,

f ( x1 ) f ( x 2 ) (. 5). f : X f ( X )

.

f ( X ) X
Y X (.5), . .
y f ( X ) E ( f ), f ( X ), ,
, x X , ,
, .

f f 1. ,
D( f ) = E ( f 1 ) = X ; E ( f ) = D( f

) = Y.

. 5
2004, . .

2004-2005 . . 4 10 . . -. . -.

, ,
D( f ) E ( f ). (, ,
.)
6. 1 .
2
.
7. y = x 3 .

f ( x1 ) f ( x2 ) = ( x1 x2 ) + x1 x2 +
f ( x1 ) = f ( x2 )
x1 = x2 , . . .
y = a
x13

x23

x12

x22

a .

x = a.

y = x 3
D( f ) = R
E ( f ) = R. f 1

D( f 1 ) = R

E ( f 1 ) = R.

: x = 3 y .
, : y = 3 x ( . 7).
y = f 1 ( x )
y = f ( x )
y = x
( x y ).

. 6

8. y = x 2 (

, D ( f ) = R ). ,
x1 0 x 2 = x1 y = x12 = x22 , . .

E ( f ) = [0;+ ).

D( f )

9. : y = x 2 , D ( f ) = [0;+ )
(.6 ). y = a, a 0
, a .
D ( f ) = [0;+ ) E ( f ) = [0;+ ) ,
f 1. : x =
2004, . .

y
6

2004-2005 . . 4 10 . . -. . -.

( )

( )

D f 1 = [0; ) E f 1 = [0; ).
y = x (. 8).
10. :
y = x 2 , D( f ) = ( ;0] ( .6 ).

( )

( )

: x = y D f 1 = [0;+ ), E f 1 = ( ;0].

y
y= x 3
y= x

y = x2

y= 3 x

. 7

y= x

. 8

3. .
f ( x ), X , () ,
x1 , x2 X , , x 2 > x1 ,

f ( x2 ) > f ( x1 )( f ( x2 ) < f ( x1 )).

,
. , ,
x1 x2 f ( x1 ) f ( x2 ), ,
.
(
).
,
x1, x2 X , x2 > x1 f ( x2 ) f ( x1 )( f ( x2 ) f (x1 )).
y = const , .

1
.
x
x ( ;0 ) (0;+ ), D( y ).
1 1 ( x2 x1 )
f ( x2 ) f ( x1 ) =
. , , x 2 > x1
=
x2 x1
x1 x2
x1 x 2 > 0 , . . , . ,
( ;0 ) (0;+ ) , D ( y )
11. y =

( ), . . x1 < 0, x2 > 0 x2 x1 > 0 f ( x2 ) f (x1 ) > 0 (


. 2).
f ( x ) () X ,
:
1. x X , x X , . .
0.
2. x X f ( x ) = f ( x ) ( f ( x ) = f ( x )).
, ,
.
2004, . .

2004-2005 . . 4 10 . . -. . -.

12. , ,
:
) y =

x,

) y = cos 4 x, ) y =

) y = x + 1 x 1, ) y =

x 3 4 sin 2 x
,
ctgx

x 1
.
x2 + 4

) y =

x , . .
D( y ) = [0;+ ) 0.
) y = cos 4 x .

x 3 4 sin 2 x
, . .
ctgx
1) D ( y ) ,
) y =

n;

+ n , n Z , 2

0;
2) x D ( y ) y ( x ) = y ( x ).
)

y = x + 1 x 1 , . .

y ( x ) = x + 1 x 1 = ( x + 1 x 1 ) = y ( x ).

) y =

x 1
, . ., ,
x2 + 4
2

0 = y (1) y ( 1) = ,
5

y (1) y ( 1).


,
.
,
.
, .
13. (, 1990, ). a ,
x 2 2a sin (cos x ) + a 2 = 0
.
, R.
, x = x0 , x = x0
. x0 x0 x0 0, , ,
. , , x = 0. ,
a

0,
x = 0 : 2a sin 1 + a 2 = 0 a =
2 sin 1.
a , ,
a . a .
a = 0 : x 2 = 0 x = 0;

a = 2 sin 1 : x 2 4 sin 1sin cos x + 4 sin 2 1 = 0


x 2 = 4 sin 1(sin cos x sin 1) 0(sin cos x sin 1) x = 0.
, a x = 0 .
2004, . .

2004-2005 . . 4 10 . . -. . -.

: 0;2 sin 1.

4.
f ( x ) X ,
T , :
1. x X , x + T X , x T X .

2. x X f ( x + T ) = f ( x ) = f ( x T ).
T , nT , n Z
. , ,
(), .
, , , y = sin x, y = cos x
T = 2 , y = tgx, y = ctgx
T = . tgx ctgx
R, .

: , y ( x ) = sin 2 x + cos 2 x ,
.

y ( x ) , . . y = sin 2 x + cos 2 x 1,
.
14. (, 1996, . -). f ( x )
T =

3 f 2 (0) + 7 f

2 . f

( 8 ), ,

( 72 ) + 4 = 0 f ( 2 ) + 3 f ( 8 ) + 209 = 0.
2

f (0) = f k 2 , k Z

f (0 ) = f

( 8 ) = f (2 2 ) = f ( 2 ) = f ( 72 ) = f (6 2 ) .

( )
) ( )

3 f 2 (0 ) + 7 f 72 + 4 = 0,
3 f 2 (0) + 7 f (0) + 4 = 0,

2
2
20
20
= 0.
= 0.
f (0) + 3 f (0) +
f 2 +3f 8 +
9

4
20

2 f (0) + 4 3 = 0 f (0) = 3 ,

16 4 + 20 0.
9
9
4
: .
3

15. (, 2000, - ).
8, ,

f (x )

f ( x ) = 8 x x
2

x [0;8]. f (2 x + 16 ) + 23 = 5 f ( x ).
f ( x ), -,
8, -, f (2 x + 16) = f (2 x ),
f (2 x + 16 ) + 23 = 5 f ( x ) f (2 x ) + 23 = 5 f (x ).
2004, . .

2004-2005 . . 4 10 . . -. . -.

, f ( x ), . .

f (2 x + n 8)

0 2 x 8 8n n 1,
0 2x + n 8 8
16 2 x 8n n 2.
.
n = 1 : 0 x 0 x = 0,

n = 0 : 0 2 x 8 0 x 4 f (2 x ) = 8 2 x (2 x ) 16 x 4 x 2 + 23 = 40 x 5 x 2 x= 1,
2

n = 1 : 0 2 x 8 8 4 x 8 f (2 x ) = f (2 x 8) = 8(2 x 8) (2 x 8)
2

16 x 64 4 x 2 + 32 x 64 + 23 = 40 x 5 x 2 x 2 + 8 x 105 = 0 x = 7.

n = 2;0 2 x 16 8 8 x 12.
.
,

1 + 8 n,7 + 8 m, n, m Z .
: 1 + 8n, 7 + 8m, n, m Z .

5.
16. ().

f ( x ) = arctg (sin 11x ) + arcctg 3 cos 2 x x ,


.
1 sin 11x 1

= arctg ( 1) arctg (sin 11x ) arctg (1) =

4
5

3 3 cos 2 x 3 =arcctg 3arcctg 3 cos 2 x arcctg ( 3 )= .


6
6
13


arctg (sin 11x ) + arcctg 3 cos 2 x
,
12
12
13
f max ( x ) =
,
12

x = + k , k Z ,

sin11x=1,
2

cos2 x= 1. sin 11 + k ( 1)11k sin 3 ( 1)11k =1k=2n1, n Z .

2
2

)
)

x = 2n


13
, n Z : f max (x ) = f + 2n =
.
2
2
12

?
17. (, 2002) a ,
a + 3 x + 2 a + x 2 + 4 x = 0

)(

1) , 2) .

)(

a + 3 x + 2 a + x2 + 4 x = 0

a + 3 x + 2 = 0 a = x + 2 3,

2
2
a + x + 4 x = 0 a = ( x + 2) + 4.

( x, a ) . ,

2004, . .

10

2004-2005 . . 4 10 . . -. . -.

3,
;
4.

1) , a =

a
a= x +2
2

a = (x +2)2+4
2) , a = const
, ,
. a , :

x + 2 3 = 4 ( x + 2)2 x + 2 =

29 1
29 7
a=
.
2
2

a > 4,

, a < 3,

a = 29 7 .
2

29 7
: 1) { 3;4}, 2) ( ;3)
(4;+ ).
2

a > 1,

;
1. sin x = a
a 1,
x = ( 1)n arcsin a + n, n Z .

a > 1,

;
2. cos x = a
a 1,
x = arccos a + 2n, n Z .

2004, . .

11

2004-2005 . . 4 10 . . -. . -.

3.
4.

tgx = a x = arctga + n, n Z .
ctgx = a x = arcctga + n, n Z .
. sin x =

1 10
1 10 1 3, K
=
= 1,K < 1.
, ..
2
2
2


1.
f (sin mx ) = 0 ( f (cos mx ) = 0 , f (tgx ) = 0 ).

f (t ) = 0, t = sin mx, tk ,
1,
sin mx = tk .
.

) F sin 2 x, cos 2 x, cos x = 0 F 1 cos 2 x, cos 2 x, cos x = 0.


) cos x, sin x.
1) a cos 2 x + b sin 2 x + c sin 2 x = 0

a cos 2 x + b sin 2 x + 2c sin x cos x=0 b tg 2 x + 2c tgx + a=0


2) a cos 2 x + b sin 2 x + c sin x cos x = d d cos 2 x + sin 2 x
(b d )tg 2 x + c tgx + (a d ) = 0.

18. (, 1995, - .) a,
cos 2 y + 4a cos y + 2a 2 + 1 = 0 .
cos 2 y + 4a cos y + 2a 2 + 1 = 0 2 cos 2 y 1 + 4a cos y + 2a 2 + 1

2(cos y + a ) = 0
2

a > 1,
cos y = a
y .
19. (, 1991, ).

x
x
x
x
+ 6 sin 2 = 3 cos + 12 cos 2 cos 3x.
4
4
2
4
x
x
x
x
16 cos 4 + 6 sin 2 = 3 cos + 12 cos 2 cos 3 x
4
4
2
4
16 cos 4

x
x
x
x

41 + cos + 31 cos = 3 cos + 61 + cos cos 3x


2
2
2
2

x
x
4 cos 2 + 2 cos (1 3 cos 3 x ) + 7 6 cos 3x = 0
2
2
x 1 + 3 cos 3 x 3 (cos 3 x + 3)(cos 3 x 1)
cos =

2
4
cos 3x 1 0 cos 3x = 1,

x 1
2

2
cos 2 = 2 x = 3 + 4n cos 3 3 + 4n 1, n Z .

) , cos kx, sin mx , . .


F (t sin kx, t cos mx ) = t n F (sin kx, cos mx ).

F (sin x, cos x ) = 0 ,

2004, . .

12

2004-2005 . . 4 10 . . -. . -.

sin mx
),
cos kx
, sin mx = 0 ( cos kx = 0 ).

t=

cos kx
sin mx

t=

3. sin ax + cos bx = 0 ( tgax + ctgbx = 0 )

sin ax + cos bx = 0

ab+ a+b

2 cos
2 = 0.
sin ax + sin bx = 0 2 sin
2
2
2

20. sin 7 x cos19 x = 0


sin 7 x sin 19 x = 0 2 sin 13x cos 6 x = 0


4 4
2

+ k

4
x
x
=

=
sin
13
0
,

4
13

+ k +

4.
cos 6 x = 0 2
4
6


3. a sin x + b cosx = 0, ab 0.

cosx = 0 sin x = 0 ;

cosx 0,
a sin x + b cos x = 0
b
arctg + k

b
a
.
tgx = x =

21. 4 sin 3 x 7 cos 3 x = 0.

7
4 sin 3 x 7 cos 3 x = 0 tg 3x = x =
4

arctg

7
+ k
4
.
3

4. sin x + cos x = a.

sin x + cos x = a

a
1,

sin x +sin x =a 2 cos x =a


4
2

x= arccos a +2k , kZ .
4
2
5. .

) .

22. (, 2001, ). cos 2 x

1
sin x =
2
3

2004, . .

13

2004-2005 . . 4 10 . . -. . -.

1
1
3
1

cos 2 x sin x = cos 2 x + sin 2 x


sin x =
2
2
2
2
3

3 sin x cos x sin x = sin 2 x sin x 3 cos x sin x 1 = 0

sin x = 0 x = n,

cos + x = 1 x = + k .
6
3 6
2
: n,

+ 2k , k .n R.

, ,
.
,
.

x = 5tg 2 x + 7.
4

23. ctg

ctg x = 5tg 2 x + 7
4

cos x + sin x
5 sin 2 x

=
+7
cos x sin x (cos x sin x )(cos x + sin x )
cos x sin x,

1 + sin 2 x = 5 sin 2 x + 7 cos 2 x 4 sin 2 x + 7 cos 2 x 1 = 0

x = 4 + arcctg 5 + n,

x = arcctg 1 + n.
4
3

) , (
cos 2 x ):
24. (,2001).

cos3 x sin 3x sin 3 x cos 3 x


+
= 3 sin 2 x cos x.
cos 2 x
cos 2 x
cos3 x sin 3x sin 3 x cos 3x
+
= 3 sin 2 x cos x

cos 2 x
cos 2 x
cos 2 x cos x sin 3 x + sin 2 x sin x cos 3 x

cos 2 x
(1 + cos 2 x )(sin 4 x + sin 2 x ) + (1 cos 2 x )(sin 4 x sin 2 x )

4 cos 2 x
cos 2 x 0,

6 sin 2 x cos 2 x
x = 2 ,

= 3 sin 2 x cos x
4 cos 2 x
sin 2 x(1 cos x )=0
x = + 2k .

k
2 ,
x=
+ 2k , k Z .
3

2004, . .

14

2004-2005 . . 4 10 . . -. . -.

25. (, 2002).

3 + cos 4 x 2(1 + cos 2 x )


3 + cos 4 x 8 cos 4 x
1
=

4(cos x + sin x )
4(cos x + sin x )
sin x
(sin x cos x )(sin x + cos x ) = 1
4 cos 2 x

4(cos x + sin x )
cos x + sin x
sin x
2

cos x + sin x 0,

sin x 0,
2
sin x sin x cos x 1 = 0 cos x(cos x + sin x ) = 0.
cos x = 0 x =
:

+ k , k Z .

+ k , k Z .

)
,
.
26.
cos 14 x cos 15 x = cos 16 x cos 17 x .

1
(cos 29 x + cos x ) = 1 (cos 33x + cos x )
2
2

31 ,

2 sin 31x sin 2 x = 0 x =


n , n Z .
2
n n
, , nZ .
:
31 2
cos14 x cos15 x = cos16 cos17

27. (,1984)

6 sin x cos 2 x = 7 sin 2 x .


6 sin x cos 2 x =

7 sin 2 x

sin 2 x 0,
sin 2 x 0,

2
6 sin x cos 2 x = 7 sin 2 x. sin x 6 cos x + 7 cos x 3 = 0.

sin x = 0;

x = n,
sin 2 x 0,

, cos x = ,

3
cos x = 2

2 sin x cos x 0 sin x 0.


1 .

1
1
x = arccos + 2n.
: arccos + 2n, n Z .
3
3
6. F (sin 2 x, (sin x cos x )) = 0 .

(sin x cos x )2 = 1 sin 2 x sin 2 x = 1 (sin x cos x )2 .


t = sin x cos x F (sin 2 x, sin x cos x ) F (1 t 2 , t ) = 0
(sin x + cos x )2 = 1 + sin 2 x sin 2 x = (sin x + cos x )2 1
t = sin x + cos x F (sin 2 x, sin x + cos x ) F (t 2 1, t ) = 0
2004, . .

15

2004-2005 . . 4 10 . . -. . -.

28.(, 1994, )

sin 2 x = cos x sin x 1.

sin 2 x = cos x sin x 1,


cos x sin x 1

cos x sin x 1 0..

sin 2 x =

2 ,
2
1 (cos x sin x ) = cos x sin x 1 cos x sin x =

1;
cos x sin x 1 0.

cos x sin x = 1

1
x = + ( 1)n +1 + n, n Z .
sin x =
4
4
2
4

+ ( 1)n +1

+ n, n Z .

7. F sin 2 n x, cos 2 m x, cos 2 x = 0 f (cos 2 x ) = 0

cos 2 = 0,

cos x 0,

2
8. F (sin x, cos x ) = 0
2tg x 1 tg 2

2 ,
F
x
1 + tg 2
1 + tg 2
2

2 f tg x = 0.
x
2

9. ,

F (sin x, cos x ) = 0 t = tg

x
.
2

x
x
x
x

F (sin x, cos x ) = 0 F 2 sin cos , cos 2 sin 2 = 0


2
2
2
2

x
cos 2 = 0,


2 x
F 0, sin 2 = 0;

cos x 0,

x
x

1 tg 2
2tg
2 x

x
x
x

2
2
2 ,
2 =0 f tg x =0.
F cos 2tg , cos 1 tg =0F
2
2
2
2
1+tg 2 x 1 + tg 2 x
2

2
2

10. a sin x + b cos x = c , ab 0 .


a
b
y ( x ) = a sin x + b cos x a 2 + b 2
sin x +
cos x
2
2
a2 + b2

a +b

2
2
a +b


b
+
2
2
a +b

1.

2004, . .

16

2004-2005 . . 4 10 . . -. . -.

a
b
,

2
2
2
2
a
b
a
b
+
+

b
a

,
,

2
2
2
2
+
+
a
b
a
b

a
b
b
a
,

m
m
,
,

a2 + b2
a2 + b2
a2 + b2
a2 + b2

( ),
.
, , ,
,
.
,
.
.

4
4
3

cos x sin x 5 cos x + sin x


5
5
5

3
3

5 sin x + arcsin 5 cos x arccos


5
5


3
3
3

5 sin + arcsin cos x+ cos + arcsin sin x 5 sin + arcsin + x


5
5
5

3
3

5 cos + arccos cos x + sin + arccos sin x


5
5

1. 3 cos x 4 sin x 5

5 cos + arccos x .
5

3
5

2. 3 cos x + 4 sin x 5 cos x

4
3

sin x = 5 sin x arcsin .


5
5

5 cos x + arccos .
5

3
4

3. 3 cos x + 4 sin x 5 sin x cos x = 5 sin x arccos


5
5

3
5 cos x + arccos .
5

, ,

a
a 2 + b2

= cos ,

b
a 2 + b2

= sin .

y ( x ) = a sin x + b cos x

y ( x ) = a 2 + b 2 sin ( x + ) , . .
a 2 + b 2 (cos sin x + sin cos x ) a 2 + b 2 sin ( + x ).
a sin x + b cos x = c
y(x ) =

2004, . .

17

2004-2005 . . 4 10 . . -. . -.

sin ( + x ) =

c
a + b2
2

29. (). a ,

a sin 3 x + 3(1 a ) cos 3 x = 2a 3

[ ; ] .
: a 1.

a sin 3 x + 3(1 a ) cos 3 x = 2a 3

a 3a + 3
2

a 3a + 3
2

2a 3

sin (3 x + ) =
cos =

3(1 a )

sin 3 x +

a 3a + 3
2

a
a 3a + 3
2

f ( x ) = sin (3 x + )

2a 3
a 3a + 3
2

, sin =

cos 3x =

3(1 a )

a 3a + 3
2

,
3

[ ; ]

1,
= 1 a 2 3a + 3= 2a 3a 2 3a + 2= 0 a=
2.
a 3a + 3
a = 1 ,
[ ; ] . .
2a 3

a = 1 : a sin 3 x + 3(1 a ) cos 3 x = 2a 3


sin 3 x = 1 sin ( 3 ) = sin 3 = 0 1.
:1.

11.
30. (,2001). tgx + tg 3 x = 4 sin x
: cos x cos 3 x 0.

sin 4 x
4 sin x cos x cos 2 x

= 4 sin x
cos x cos 3 x
cos x cos 3x
sin x cos 2 x = sin x cos 3 x

sin x = 0 x = k ,
sin x 0,

sin x(cos 2 x cos 3x ) = 0; sin x 0,

cos 2 x cos 3x = 0;

sin x < 0,

cos 2 x + cos 3x = 0.

2004, . .

18

2004-2005 . . 4 10 . . -. . -.

x = k ,
sin x 0,

2k
5 x

,
x
sin sin = 0 x = 5

2
2
2k ;

sin x > 0,

(2n + 1)
,
x
5 x

5
cos 2 cos 2 = 0 x =

(2k + 1).
5n,
2k
6k
2k
2k
x=
0, cos
0, sin
0, k = 5n + 1,
: cos
5
5
5
5
5n + 2.

x=

(2n + 1)
5

: cos

(2n + 1)
5

0, cos

(2n + 1)
6 (2n + 1)
0, sin
=
5
5

5k + 3,
2n
= sin +
< 0, n =
5
5
5k + 4.

k ,

2 + 2k ,
k ,
5

4
2

x=
+ 2k , x =
+ k ,
5
5
4
7

+ 2k ,
+ k .

5
5

9
5 + 2k .
2
4
: k ,
+ k ,
+ k , k Z .
5
5
12.
31. sin 8 x cos5 x = 1.
sin 8 x cos5 x = 1

sin 8 x cos5 x = sin 2 x + cos 2 x

sin 2 x 1 sin 6 x + cos 2 x 1 + cos3 x = 0.

2004, . .

19

2004-2005 . . 4 10 . . -. . -.

sin 2 x = 0,
;
2
cos x = 0;

2
sin x = 0,
x = (2n + 1), n Z ;

+
=
x
1
cos
0
;

6
sin x = 1, x = + k , k Z ;
cos 2 x = 0;
2

sin 6 x = 1,

.
cos3 x = 1;
: (2n + 1),

+ n, n Z .

1(2). , 0 x

x?
2

3
,
2

sin 2 x = sin

2(2). (, 1995, ) x , ,
1, x + 2, sin (arcsin x ) , ,
.
3(2). (, 2000, - .) 20 cos( ) ,
: cos + cos = 0,3; sin + sin = 1,1 .

4(2). (, 1996, ) cos 4 x + sin x sin 3 x = 0 .

3 1
3 + 1
x cos
x = 1.
2

6(2). (, 1981, ) cos 2 x


= sin (4 x + 3 ) .
2

7(2). (, 1995, ) cos 2 x = 2(cos x sin x ) .

5(2). (, 1996, . -) cos

5 sin x + cos 2 x + 2 cos x = 0,


0o ;360o .
8(2).

9(2). y ( x ) = x 2 2 x

[ 2;2].

10(2). f ( x ) = 2 x 2 x 4 -

[ 2;2].

11(2).

y = 2 cos 2 x 12 cos x + 15 .
12(2). y = 2 cos 2 x + 4 sin x + 1.
13(2).

f ( x ) = x 3 x = 2 .

2004, . .

20

2004-2005 . . 4 10 . . -. . -.

tg 4 x
11

.
4 x + tgx = 3 1
ctgx
2

2(5). (, 2003) sin x + cos x + sin 4 x = cos 2 x.


1(2). (, 2003, . -.) ctg

cos 5 x cos 3 x sin 3x sin 5 x


= 2 sin 2 x.
cos 2 x
4(4). (, 2004) cos 3 x + cos 2 x = 3 cos x cos 4 x.
3(4). (, 2003)

5(3). (, 2004) sin x 1 cos x 2 sin x = sin x + cos x.


6(3). (, 2003, )

x
x

cos x + cos
5 cos(2 x + ) 5 + 9 sin x + = 0.
2
2
2

7(4). (, 2003, ) ,
sin

sin arccos(5 x ) = + arcsin sin (7 x 3)


.

:
8(4). (, 1981)

2 cos 2 x = (1 tgx )(1 + sin y + sin 2 x ),

8
8
2
8 cos 2 x cos x sin x + 1 = 25 cos y.

9(5). (,1982)

3 cos(4 x 2 y ) = 2 cos(2 x 2 y ),

2 sin ( x + y ) = 3 sin ( y x ).
cos x

sin x sin ( x + y ) = 2 ,
10(3).
sin x sin y = 1 .

4
sin y = sin x cos(x + y ),
11(3).
sin y cos( x + y ) = sin x.

2004, . .

21